2011
DOI: 10.1177/2150129710397659
|View full text |Cite
|
Sign up to set email alerts
|

Framing Asthma

Abstract: Little is known about the portrayal of asthma in US newspapers. The purpose of the present study was to analyze 7 representative US newspapers to determine the frequency of substantive asthma articles and the occurrence of stigma, challenge, fear, and management frames within the articles. The authors conducted a content analysis of 203 in-depth asthma articles from 2 years in 7 US newspapers and developed a coding instrument to identify framing cues of stigma versus challenge and fear versus management. Resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 13 publications
2
10
0
Order By: Relevance
“…Though, series of relevant academic studies and research efforts on media framing to be specific (Adeyanju & Oriola, 2010;Joffe & Haarhoff, 2002;Ungar, 1998) were conducted on Ebola in its previous outbreaks in countries order than Nigeria, which was at low key compared to the 2014 experience. Studies have also been conducted on the media framing of other outbreaks such HIV/AIDS (Bleich, 2007;Wu, 2006); Asthma (Johnson et al, 2011); SARS (Tian & Stewart, 2005); and Flu (Nerlich & Jurnal Komunikasi Malaysian Journal of Communication Jilid 32 (2) 2016: 362-380 ___________________________________________________________________________…”
Section: Media Framing Of Ebola: Between Issue Reportage and Public Hmentioning
confidence: 99%
“…Though, series of relevant academic studies and research efforts on media framing to be specific (Adeyanju & Oriola, 2010;Joffe & Haarhoff, 2002;Ungar, 1998) were conducted on Ebola in its previous outbreaks in countries order than Nigeria, which was at low key compared to the 2014 experience. Studies have also been conducted on the media framing of other outbreaks such HIV/AIDS (Bleich, 2007;Wu, 2006); Asthma (Johnson et al, 2011); SARS (Tian & Stewart, 2005); and Flu (Nerlich & Jurnal Komunikasi Malaysian Journal of Communication Jilid 32 (2) 2016: 362-380 ___________________________________________________________________________…”
Section: Media Framing Of Ebola: Between Issue Reportage and Public Hmentioning
confidence: 99%
“…Quantitative content analysis of publicly accessible online documents from NZ PSOs, press, and DTCA from manufacturers between 2014 to 2019 was conducted, an approach commonly used to analyse media messages (25), and informed by previous literature (13,19,26,27). This approach uses prior research to identify key concepts as initial coding categories, similar to the approach reported by similar studies (13,28).…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that the general public relies heavily on mass media for health information (10,11), and the way health issues are presented in the media can in uence the perceptions of health conditions by the public (12)(13)(14). Media representations of asthma and asthma treatments, therefore, have the potential to in uence people's beliefs about their illness and medications (12), and in uence adherence (15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…I selected these news outlets because they are widely read, highly accessible, and easy to search. These particular newspapers have an "agenda-setting influence" as well as a wide circulation (Johnson et al, 2011). Further, the three newspapers have different political biases, and it was hoped that this political diversity would yield a more varied representation of youth crime stories.…”
Section: Quantitative Analysismentioning
confidence: 99%